2015
DOI: 10.1111/cdev.12332
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Processes in Low‐Socioeconomic Status Bilingual Children: Are They Modulated by the Amount of Bilingual Experience?

Abstract: Recent research indicates that bilingual children are more proficient in resolving cognitive conflict than monolinguals. However, the replicability of such findings has been questioned, with poor control of participants' socioeconomic status (SES) as a possible confounding factor. Two experiments are reported here, in which the main attentional functions and pragmatic ability of 54 bilingual and 56 monolingual low-SES children were assessed (Experiment 1: 6- to 12-year-olds; Experiment 2: 6- to 8-year-olds). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 97 publications
3
51
0
1
Order By: Relevance
“…Also, the results are consistent with the interpretation that the heightened attentional abilities of bilinguals, notably selective attention, are shaped by ongoing bilingual experience. However, converging evidence from the Ladas et al () study suggested that there was an overall lack of bilingual advantage in tasks of attentional control in low SES bilingual immigrants (Greek–Albanian, ages 6–8) children. This counteracts several previous findings that showed a bilingual edge.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Also, the results are consistent with the interpretation that the heightened attentional abilities of bilinguals, notably selective attention, are shaped by ongoing bilingual experience. However, converging evidence from the Ladas et al () study suggested that there was an overall lack of bilingual advantage in tasks of attentional control in low SES bilingual immigrants (Greek–Albanian, ages 6–8) children. This counteracts several previous findings that showed a bilingual edge.…”
Section: Resultsmentioning
confidence: 97%
“…According to earlier research by Rueda, Posner, Rothbart, and Davis‐Stober (), this area of human development deals with the ability to allocate attention to relevant objects or locations (orienting), maintaining a state of readiness (alertness), and selecting the most goal‐relevant response (executive control). Studies in this theme explored the relationship between bilingualism and selective attention (Blom, Boerma, Bosma, Cornips, & Everaert, ; Chung‐Fat‐Yim, Sorge, & Bialystok, ), attentional processes in low SES bilingual children (Ladas, Carrol, & Vivas, ; Yang & Yang, ), and the role of attentional control in senior adults (Ong, Sewell, Weekes, McKague, & Abutalebi, ). Collectively, the findings supported the bilingual advantage in attentional control tasks and particularly stressed the positive impact of early childhood and adult bilingualism on the attentional system.…”
Section: Resultsmentioning
confidence: 99%
“…Together, these findings are consistent with previous studies showing that characteristics of the quantity and quality of the bilingual experience have an effect on bilinguals' IC development. Bilinguals with more balanced proficiency across languages tend to be faster at resolving cognitive conflict (Ladas, Carroll, & Vivas, ; Yow & Li, ). Longer exposure to the second language has also been associated with higher IC performance, both in toddlers (Poulin‐Dubois, Blave, Coutya, & Bialystok, ) and in school‐aged children attending language immersion programs (Bialystok & Barak, ).…”
Section: Discussionmentioning
confidence: 99%
“…A criticism of previous studies testing the bilingual advantage by comparing groups of monolingual and bilingual individuals from different cultural backgrounds has been that the bilingual advantage observed is driven by cultural differences that are confounded with bilingualism, rather than by experience managing two languages per se (Hilchey & Klein, ; Ladas et al., ; Morton & Harper, ). Researchers have tried to address this potential confound by comparing bilingual individuals to monolingual peers who share and do not share the same cultural background (Yang, Yang, & Lust, ), or by showing a bilingual advantage in bilinguals of different cultural backgrounds and in different geographical regions (Barac & Bialystok, ; Bialystok, Barac, Blaye, & Poulin‐Dubois, ; Bialystok & Viswanathan, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation